Mental Health in Developing Countries: Challenges and Opportunities in Introducing Western Mental Health System in Uganda - Janice Katherine Kopinak, MHSc, MSc, RN (Global Health and Education Projects, Inc., 2014)
Background: Despite decades of disagreement among mental health practitioners and researchers in the Western world pertaining to the causation, classification and treatment of mental disorders there is an ongoing push to implement western mental health models in developing countries. Little information exists on the adaptability of western mental health models in developing countries. Method: This paper presents a review of the attempt to implement a western-oriented mental health system into a different culture, specifically a developing country such as Uganda. It draws upon an extensive literature review and the author's work in Uganda to identify the lessons learned as well as the challenges of introducing a western-oriented mental health system in a totally new cultural milieu. Results: There is recognition by the national government that the challenges faced in mental health services poses serious public health and development concerns. Efforts have and are being made to improve services using the Western model to diagnose and treat, frequently with practitioners who are unfamiliar with the language, values and culture. Conclusions and Global Health Implications: Uganda can continue to implement the Western mental health practice model which emanates from a different cultural base, based on the medical model and whose tenets are currently being questioned, or establish a model based on their needs with small baseline in-country surveys that focus on values, beliefs, resiliency, health promotion and recovery. The latter approach will lead to a more efficient mental health system with improved care, better outcomes and overall mental health services to Ugandan individuals and communities. Key Words: Mental health • Models • Implementation • East Africa • Uganda. Copyright © 2015 Kopinak. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.